Emerging soft conductors for bioelectronic interfaces - Gao, Dace (2021)
Bidirectional interfacing between electrodes and biological systems has enabled diagnostics and therapeutics in modern medicine, however the inherent dissimilarity between the soft, ion-rich, dynamic biological tissues and the rigid, dry, static electronic systems hinders the establishment of effective and reliable bioelectronic interfaces. In the past decade, the scope of flexible/ stretchable electronics has been broadened into bioelectronics owing to the need of implementation of various biocompatible soft conductors. Herein, the basic requirements for the construction of both epidermal and implantable bioelectronic interfaces utilizing soft materials are discussed, the most recent progress in the development of soft conductors, which are customized to interface with skin and other tissues, are summarized. An outlook into the remaining obstacles is provided and possible strategies to facilitate technological advances in bioelectronics are also outlined.